ROLE OF TENURE IN THE FESIBILITY OF WHEAT PRODUCTION PROJECTS IN DHI- QAR GOVERNORNORATE - & Izz al-Din, Barbaz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Projects of various sizes and types are the most important factors for the success of economic development plans in general. Agricultural projects and agricultural cooperatives are also considered as the basis for agricultural development in the economies of many countries. One of the most important targets of development is to fight poverty and famine, and achieving that depends on how to deal with agricultural lands with good management and scientific methods. The aim of this research is to identify the economic feasibility of one of the agricultural activities in the province of Dhi Qar. The study included 132 farms specialized in the cultivation of wheat crop in the province of Dhi Qar for the agricultural season 2017-2018. The results of the research showed that the projects in the province have economic and technical efficiency and proved the results of the economic feasibility criteria of investment in such projects. The researchers found that the size of the possession 30-50 dunums has both productive and technical efficiency, while the farmers with holdings of more than 50 dunums has the best economic efficiency in the use of available resources, despite the low productivity if the return on investment about 188% in small farms, while the profitability of about 119% dinars, while the capital productivity amounted to about 2.081 dinars, and therefore the researchers recommended the need to encourage investment in the large plants given their ability to absorb technology, reduce average production costs and intensify other resources.